INVESTIGATION OF THE CREEP EFFECT ON THE STRESS-STRAIN STATE ON TIMBER-REINFORCED CONCRETE MULTISTOREY BUILDINGS (Collection of scientific works «Modern structures of metal and wood», 2024)
In the conditions of military aggression against Ukraine, a special attention should be payed to the development of innovative solutions in various fields, which will allow effective rehabilitation of veterans and civilians. The building as an artificial environment is an integral part of how a person experiences trauma and has the potential to calm the body's response to perceived stressors by modulating and leveling the surrounding triggers. The development of project based on the concept of biopositive design involves taking into account the criteria of biophilic design, the use of "green" environmentally safe materials and resource-efficient structural solutions. The  article  presents  the  results  of  the  experimental  design  of  a  biopositive  rehabilitation building using the example of a prototype project of a residential block. The proposed structural solution of a biopositive building-prototype consisting of modular prefabricated elements: three-layer panels for walls and roof, consisting of two layers of cross-glued wood, connected with each other by flexible ties, and heat and sound insulation arranged between the layers made of an effective environmentally friendly material; ribbed floor panels consisting of glulam beams and cross-glued wood slabs, joined together with high-strength bio-based non-formaldehyde glue. To substantiate the proposed structural solution of the biopositive building, a study of the stress-strain state was carried  out using the  LIRA-CAD software complex. Theoretical provisions were formulated and an assessment of the degree of utilization of the load-bearing capacity of structural elements made of cross-laminated and glued laminated timber as well as an analysis of deflections and displacements was carried out. The degree of utilization of the load-bearing capacity of the floor panel in terms of normal stresses from the action of the bending moment is 45%, in terms of shear stresses is 18%. For wall and roof panels under the simultaneous action of compressive and bending stresses, the degree of utilization of the load-bearing capacity is 58%. The calculated floor deflection considering creep deformations and the maximum horizontal displacements from the wind load do not exceed the maximum allowable values.